ESTABLISHMENT AND DEVELOPMENT OF A MODERN SYSTEM OF HIGHER PEDAGOGICAL EDUCATION OF THE GREEK REPUBLIC AS A COUNTRY - MEMBER OF THE BLACK SEA ECONOMIC COMMUNITY (Pedagogy of Higher and Secondary Education, 2011)
The article considers the process of becoming and development of high pedagogical education's system in Republic of Greece as the country-member of the Black Sea economical cooperation.
Keywords: high pedagogical education; teachers' training; pedagogical staff; system